2013
DOI: 10.1089/jwh.2012.4222
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Intimate Partner Violence and Preventive Screening Among Women

Abstract: The strongest association between IPV and preventive screening was seen for HIV testing, which likely reflects the women's perceived risk for HIV infection. That these women are in contact with the healthcare system provides support for recommendations for widespread adoption of IPV screening and counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…75,76 In one of the only population-based studies on IPV and specific preventive screening behaviors in women, those who had lifetime experiences of IPV were more likely to undergo HIV testing, cervical cytology, and breast examinations compared to those without IPV experiences. 77 However, women exposed to IPV tended to be less likely to obtain passive preventive screening tests such as mammography screening conducted in the context of routine physical care compared with women unexposed to IPV. 77 This discrepancy may be related to insurance coverage and socioeconomic status.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…75,76 In one of the only population-based studies on IPV and specific preventive screening behaviors in women, those who had lifetime experiences of IPV were more likely to undergo HIV testing, cervical cytology, and breast examinations compared to those without IPV experiences. 77 However, women exposed to IPV tended to be less likely to obtain passive preventive screening tests such as mammography screening conducted in the context of routine physical care compared with women unexposed to IPV. 77 This discrepancy may be related to insurance coverage and socioeconomic status.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…77 However, women exposed to IPV tended to be less likely to obtain passive preventive screening tests such as mammography screening conducted in the context of routine physical care compared with women unexposed to IPV. 77 This discrepancy may be related to insurance coverage and socioeconomic status. Expanding upon these findings, a prospective longitudinal study of 1,420 women found that IPV exposure increased the odds of receiving counseling for safety and violence in the home (although the overall rate was only 20%) and screening tests for HIV/STIs; no associations were observed for IPV exposure and Pap testing, contraceptive counseling, alcohol and drug use counseling, and smoking counseling.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Several studies have shown that women experiencing IPV may in fact receive more preventive services, particularly those related to sexual health (e.g., STI/HIV testing) than those not experiencing IPV. [76][77][78] Given the relatively frequent follow-up required for PrEP, however, it is unclear as to whether these findings are applicable in this context.…”
Section: Difficulties With Covert Usementioning
confidence: 99%
“…IPV and fear of IPV have been associated with substance use, multiple sex partners, and exchange sex, coercive sex, challenges negotiating safe sex, having sex with men who are HIV-positive or have HIV risk factors such as injection drug use, and increased risks for HIV and other sexually transmitted infections (STIs). 6,7 Although IPV survivors may be more likely to get tested for HIV than women who do not experience IPV, 8 fears of IPV can complicate and even deter disclosure of HIV or other STIs by women to their male partners, since it can trigger violence. 9,10 IPV can be a formidable barrier to access of health care for women living with HIV.…”
Section: Introductionmentioning
confidence: 99%